Earliest triassic conodonts of Gua Panjang, Merapoh, Pahang and their bearing towards Permian-Triassic Mass extinction in Malaysia - Nelisa Ameera Mohamed Joeharry,; Mohd Shafeea Leman,; Che Aziz Ali,; Kamal Roslan Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2018)
A single sample from the logged section at eastern side of Gua Panjang limestone hill, southwest of Kampung Kubang Rasa Village, Merapoh, has yielded 5 very important conodont species. They are Hindeodus parvus erectus, Hindeodus parvus parvus, Hindeodus latidentatus latidentatus, Hindeodus latidentatus praeparvus, Hindeodus postparvus, Hindeodus eurypge and Isarcicella staeschi. These Early Triassic conodonts were obtained in a bioclastic dolostone sample, located 2.5 m above bioclastic grainstone which yielded Late Permian foraminifera. The conodonts found were given Conodont Alteration Index (CAI) scale of 5, consistent with the heating of Main Range granitoid during Indosinian Orogeny. Limestone harbouring basal Triassic conodonts in Gua Panjang is interpreted to be deposited in an open shallow marine shelf environment.